Model Sistem Pendukung Keputusan untuk Strategi Pemasaran Digital UMKM Handmade: Sebuah Pendekatan Konseptual Berbasis DEAHP - Zuhrufillah, Irfani (Universitas Harapan Bangsa, 2025)
Micro, Small, and Medium Enterprises (MSMEs), particularly the handmade crafts sector, are a vital part of Indonesia’s economy with significant potential but face challenges in digital marketing and capital access. This study proposes a Decision Support System (DSS) model combining Analytical Hierarchy Process (AHP) and Data Envelopment Analysis (DEA) to assist MSME actors in selecting effective digital marketing strategies. AHP is used to determine priority weights of key marketing criteria such as cost, market reach, and customer satisfaction. These weights serve as constraints in an input-oriented DEA model to measure the relative efficiency of digital marketing alternatives: social media, marketplaces, and official websites. Optimization results indicate that marketplaces achieve the highest efficiency score (1.00), followed by official websites (0.95) and social media (0.83). With DSS, business owners can develop more targeted and sustainable marketing strategies based on objective data. This DEAHP approach offers a systematic, data-driven framework for decision-making in digital marketing for handmade MSMEs, particularly in Kota Luwuk, supporting enhanced competitiveness and marketing performance. The model serves as a conceptual foundation for further empirical research. The aim of this research is to provide an understanding of how the application of an AHP and DEA-based decision support system can assist SMEs in designing more efficient digital marketing strategies.